2013
DOI: 10.1021/am402350n
|View full text |Cite
|
Sign up to set email alerts
|

Porous TiO2/C Nanocomposite Shells As a High-Performance Anode Material for Lithium-Ion Batteries

Abstract: Porous TiO2/C nanocomposite shells with high capacity, excellent cycle stability, and rate performance have been prepared. The synthesis involves coating colloidal TiO2 nanoshells with a resorcinol-formaldehyde (RF) layer with controllable thickness through a sol-gel-like process, and calcining the composites at 700 °C in an inert atmosphere to induce crystallization from amorphous TiO2 to anatase and simultaneous carbonization from RF to carbon. The cross-linked RF polymer contributes to the high stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
89
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 23 publications
4
89
1
Order By: Relevance
“…[29][30][31][32][33][34][35][36][37] The two-dimensional and three-dimensional structure of graphene/TiO 2 , resulting from random pathways in these composites, can dramatically slow down the rate of electron transfer, which thus results in unexpected loss of electrons compared to the one-dimensional structure. [35][36][37] Furthermore, to investigate the effect of morphology on the performance of one-dimensional graphene/ TiO 2 structures, several types of morphologies including nanoparticles, nanowires, nanofibers, and other morphologies have been synthesized. [29][30][31][32][33][34][35] Among them, nanowires and nanofibers show better performance owing to their high surface to volume ratio and their effective electrontransfer pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31][32][33][34][35][36][37] The two-dimensional and three-dimensional structure of graphene/TiO 2 , resulting from random pathways in these composites, can dramatically slow down the rate of electron transfer, which thus results in unexpected loss of electrons compared to the one-dimensional structure. [35][36][37] Furthermore, to investigate the effect of morphology on the performance of one-dimensional graphene/ TiO 2 structures, several types of morphologies including nanoparticles, nanowires, nanofibers, and other morphologies have been synthesized. [29][30][31][32][33][34][35] Among them, nanowires and nanofibers show better performance owing to their high surface to volume ratio and their effective electrontransfer pathways.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] Furthermore, to investigate the effect of morphology on the performance of one-dimensional graphene/ TiO 2 structures, several types of morphologies including nanoparticles, nanowires, nanofibers, and other morphologies have been synthesized. [29][30][31][32][33][34][35] Among them, nanowires and nanofibers show better performance owing to their high surface to volume ratio and their effective electrontransfer pathways. [35] For example, Pan et al reported that www.eurjic.org FULL PAPER the photocatalytic activity of graphene/TiO 2 nanowires is higher than that of graphene/TiO 2 nanoparticles and pure nanowires or nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, TiO 2 -based anodes for LIB applications have been extensively studied . These studies include different morphologies of titania as well as different crystal structures, and combinations of titania with other materials to enhance cycling and rate performance [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, however, it is the properties of the nanospheres, whether porous [105,110,111] or dense [96,97,104,112] While these types of nanoparticles can be synthesized at the lab scale, commercial scaling is potentially more complicated and costly because of the expensive organic precursors and the acidic environment required [112] or the need for dropwise addition of an acidic solution to produce porous spheres [111]. However, advances in aqueous-based synthesis of TiO 2 may provide commercially scalable synthesis routes for not only anatase nanoparticles [12], but other phases and morphologies of TiO 2 [116,117] …”
Section: Anatasementioning
confidence: 99%